Impacts of Financial, Food, and Fuel Crisis on the Urban Poor - Baker, Judy L. (World Bank, Washington, DC, 2012)
The effects of the recent financial crisis are only beginning to be felt in many developing countries, but economic activity is declining rapidly with far reaching impacts. This crisis comes at a time when most countries are still struggling with the impacts of rising food and fuel prices. Though global food and fuel prices have softened somewhat in recent months from the highs earlier in 2008, there has been much volatility and they are anticipated to remain high over the medium term. It is estimated that the high food and fuel prices alone have increased the number of extremely poor in the world by at least 100 million. While impacts of the crises affect both urban and rural populations, the urban poor have been hit hardest in this recent food and fuel crisis, and in previous financial crisis, given their heavy reliance on the cash economy, no agricultural production to fall back on, and wage reductions and employment losses at urban based industries. This has resulted in social unrest in a number of cities earlier in 2008 all over the developing world.